2011
DOI: 10.3855/jidc.1212
|View full text |Cite
|
Sign up to set email alerts
|

Ventilator-associated pneumonia in Iranian intensive care units

Abstract: Introduction: Nosocomial pneumonia (NP) and ventilator associated pneumonia (VAP) occur most frequently in intensive care units (ICU). This study seeks to determine the etiological agents of NP and VAP along with their antibacterial susceptibility patterns, and to evaluate the factors contributing to patient mortality. The impact of appropriate therapy in terms of three parameters (body temperature, PaO2/FiO2 ratio and leukocyte count) was also assessed. Methodology: This study involved 836 adult patients admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
19
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 33 publications
7
19
0
2
Order By: Relevance
“…According to our data, in VAP patients not tracheotomized during ICU stay, the mortality was approximately two-fold higher than in patients tracheotomized either before or after VAP onset. Other predictors positively correlated with lethal outcomes were duration of MV and use of corticosteroids, which is consistent with the results of many other studies 3,[13][14][15]29 . Koleff et al also found the mortality of patients receiving tracheotomy to be lower than the mortality of non-tracheotomized patients 17 .…”
Section: Discussionsupporting
confidence: 81%
“…According to our data, in VAP patients not tracheotomized during ICU stay, the mortality was approximately two-fold higher than in patients tracheotomized either before or after VAP onset. Other predictors positively correlated with lethal outcomes were duration of MV and use of corticosteroids, which is consistent with the results of many other studies 3,[13][14][15]29 . Koleff et al also found the mortality of patients receiving tracheotomy to be lower than the mortality of non-tracheotomized patients 17 .…”
Section: Discussionsupporting
confidence: 81%
“…In another study conducted in southern Iran, A. baumannii was also ranked as the first agent. However, S. aureus was found to be the second most common agent of ventilator-associated pneumonia [8].…”
Section: Discussionmentioning
confidence: 99%
“…were more common in patients with HAP (15). This difference might be due to different local epidemiology, different patient populations and study designs, since the current study evaluated ICU admitted patients with HAP, but Japoni et al (15) studied patients with VAP.…”
Section: Discussionmentioning
confidence: 72%
“…In the current study, carbapenem was the most widely used antibiotic while in the study by Japoni et al (15) carbapenem was the most common form of antibiotic. Salehifar et al (14) showed that ceftazidime was used more frequently and most effective antibiotic on Pseudomonas spp.…”
Section: Discussionmentioning
confidence: 98%